Peran Linguistik Terapan dalam Transformasi Pendidikan Islam - Mulya Putra; Muhammad Miftah Al-Khalili; Attala Rania Insyra Pasaribu; Sakholid Nasution (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explain the linguistic approach, one of the methods used in Islamic teaching. One of the options in Islamic education is linguistics, which aims to investigate the principles of Islamic education before trying to offer meanings that are in line with the difficulties and developments of today's era. To build the main core covering the linguistic approach in Islamic education, this study uses a literature study technique, which involves collecting reference sources that are considered relevant to the research problem and then distributing them. The results of the study, language is a sound sign that is considered to reflect how human reason and emotion are perceived. Humans use this sound sign to validate their internal identity and their perception of the surrounding environment. To keep Islamic teachings in line with the current cycle of development and change, this study effectively shows the important function that language plays in articulating it. The noble and moderate teachings of Islam can be misinterpreted by linguists.